HELICAL WINDING INDUCTION HEATING SYSTEM (Journal of Engineering, 2007)
A novel method in induction heating is presented. The winding of the excitation coil is helical and of three –phase type while the charge is cylindrical. This heating system is compared with the classical induction heatingsystem of the circular coil type with cylindrical charge and single – phase excitation. The study shows the meritsof the proposed new system over the conventional one. The multi – layer theory approach is adopted for theanalysis of helical winding induction heating system which is an analytical method.